Should metal alloy discs be used for patch testing in suspected metal implant intolerance reaction? - Thomas, P.; Geier, J.; Dickel, H.; Diepgen, T.; Hillen, U.; Kreft, B.; Schnuch, A.; Szliska, C.; Mahler, Vera (Orthopäde, 2015)
Intolerance reactions to metal implants may be caused by metal allergy. However, prior to implantation, patch testing should not be done in a prophylactic-prophetic approach. Pre-implant patch testing should only be performed to verify or exclude metal allergy in patients with a reported respective history. In the case of implant-in particular arthroplasty-related complications like, for example, pain, effusion, skin changes, reduced range of motion, or loosening, orthopedic-surgical differential diagnostics should be performed first. Allergological workup of suspected metal implant allergy should be done with the DKG baseline series which contains nickel-, cobalt- and chromium-preparations. Various studies assessing the usefulness of metal alloy discs for patch testing proved that this approach does not give reliable information about metal allergy. Positive patch test reactions to the discs cannot be assigned to a specific metal within the disc alloy components. Furthermore, availability of such metal discs might be an invitation to uncritical testing. Accordingly, due to lack of benefit in comparison to patch testing with standardized metal salt preparations, we do not recommend patch testing with metal alloy discs.
EVALuna2:19556